Pengaruh Model Pembelajaran Kooperatif Tipe Time Token Terhadap Hasil Belajar Bahasa Indonesia Siswa SD - muhammad asrul sultan; Deddy Bambang Irawan; Rosdiah Salam (JIKAP PGSD: Jurnal Ilmiah Ilmu Kependidikan, 2020)
: This research to find out whether there is the influence of the cooperative to time token type learning model on the learning outcomes of Indonesian language speaking skills in fifth grade students of SD Negeri 1 Massepe. This research uses a quantitative approach to the type of experimental research and uses a Pre-Experimental design in the form of One Group Pre-test - Post-test Design. The sampling technique used in this study was purposive sampling technique with a sample of 15 students. The results of hypothesis testing using the One Sample T-Test test obtained a significance of 0.00 (0.00 <0.05) the average score of the pretest was smaller than the average score of the posttest or µ1 ˂ µ2 indicating that H0 was rejected and Ha was accepted which means there are differences in the average results of speaking skills of fifth-grade students of  SDN  1  Massepe on  Indonesian language subjects between before and after the use of cooperative learning models of time token types. Based on these results it can be concluded that there is the influence of the cooperative to time token type learning model on the learning outcomes of Indonesian speaking skills in fifth grade students of SD Negeri 1 Massepe.